1996
DOI: 10.1136/bmj.312.7022.13
|View full text |Cite
|
Sign up to set email alerts
|

A randomised prospective comparison of percutaneous endoscopic gastrostomy and nasogastric tube feeding after acute dysphagic stroke

Abstract: This study indicates that early gastrostomy tube feeding is greatly superior to nasogastric tube feeding and should be the nutritional treatment of choice for patients with acute dysphagic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
0
17

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(168 citation statements)
references
References 14 publications
2
144
0
17
Order By: Relevance
“…Very recently, a randomized prospective study of thirty in-patients with persistent dysphagia 14 d following acute stroke, compared percutaneous gastrostomy and nasogastric tube feeding. Patients fed via the gastrostomy tube had significantly lower mortality and a greater improvement in nutritional status at 6 weeks (Norton et al 1996). In a double-blind placebo-controlled trial, ninety-six independently-living, healthy men and women over 65 years of age were randomly assigned to receive nutrient supplementation.…”
Section: Improving Nutritional Status In Hospital and Its Relation Tomentioning
confidence: 99%
“…Very recently, a randomized prospective study of thirty in-patients with persistent dysphagia 14 d following acute stroke, compared percutaneous gastrostomy and nasogastric tube feeding. Patients fed via the gastrostomy tube had significantly lower mortality and a greater improvement in nutritional status at 6 weeks (Norton et al 1996). In a double-blind placebo-controlled trial, ninety-six independently-living, healthy men and women over 65 years of age were randomly assigned to receive nutrient supplementation.…”
Section: Improving Nutritional Status In Hospital and Its Relation Tomentioning
confidence: 99%
“…1 Previous studies have demonstrated mortality and nutritional benefits of gastrostomy feeding in certain subgroups of patients. 2,3 However, the demands for this procedure have increased, including conditions where the evidence base is often lacking. 4,5 This is highlighted by the rise in individuals receiving home enteral nutrition via their gastrostomy tubes.…”
Section: Introductionmentioning
confidence: 99%
“…1 The benefit of gastrostomy insertion, with regard to morbidity and mortality, has been demonstrated in patients with cerebrovascular disease and oropharyngeal malignancy. [2][3][4] However, the demands for PEG insertion have risen to include conditions where the indications and long-term outcome are uncertain. 5,6 Dementia is an ever more common reason for PEG insertion when the patient cannot or will not eat.…”
mentioning
confidence: 99%